(untitled) (Ágora de Heterodoxias, 2021)
Fertility is the demographic variable that received the most attention in population studies, evidence of this is the pronatalist and ant natalist programs that are developed as part of the health programs in the countries. From the care economy approach, it is possible to complement the demographic view of fertility, being able, in addition to explaining social behaviors, to provide solutions through work and family reconciliation strategies. European countries were the first to identify this need, and in the Latin American region it is an application issue for some countries and is still under discussion in others. Based on a bibliographical-documentary and statistical review of certain variables, this work analyzed the policies of work and family reconciliation that help to increase the fertility levels of the countries from the perspective of care